STUDY ACCEPTANCE OF CONSUMER ON ATOM FORTIFIED CRACKERS FISH BONE MEAL OF MILKFISH (Chanos chanos) - Helmi Rialdi; Dewita '; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was aimed to determine the effect atom fortified crackers fish bone meal of Milkfish (Chanos chanos) on consumer acceptance atom crackers and to determine the best amount fish bone meal on processing atom crackers of Milkfish. The method was used experiment with a Completely Randomized Design (CRD) non factorial. The parameters were observed organoleptic test, moisture content, ash, calcium and phosphor. The results is showed that based on parameters tested, so the best treatment on crackers atom is used formulation bone meal of Milk fish 50g with the caracteristic a golden yellow; typical aromatic atom crackers; typical atom crackers tasted: the texture are dry and crispy, with the chemical composition are 5.36% moisture content, 3.69% ash, calcium and phosphor are 5257.11 mgCa/100 gr, 1164.48 mgP/100 gr respectively.Key words : Milkfish, atom crackers, fish bone meal, consumer acceptance